Formation of a Favorable Investment Climate (Britain after Brexit and Others) - Дергач, Анна Вадимівна; Дергач, А. В.; Дергач, Анна Вадимовна; Dergach, Anna; Derhach, Anna V.; Кібік, Ольга Миколаївна; Кібік, О. М.; Кибик, Ольга Николаевна; Kibik, Olha M.; Скрипник, Світлана Валентинівна; Скрипник, С. В.; Скрипник, Светлана Валентиновна; et al. (Magnanimitas Assn., 2021)
Over the years, monetary, fiscal and investment policies have determined the level of foreign investment attraction in the EU. Despite the constant reduction of real interest rates in the EU and the supranational level of the investment policy of the European Parliament, the question of the importance of EU policy in attracting investors' funds arises. The aim of the article was to identify the main factors of the investment climate and attraction of foreign investment in the EU.

Ціль статті – виявити основні фактори інвестиційного клімату процесу залучення іноземних інвестицій до Європейського Союзу. Ціль статті – виявити основні фактори інвестиційного клімату та залучення іноземних інвестицій в ЄС. Цель статьи – выявить основные факторы инвестиционного климата и привлечение иностранных инвестиций в ЕС.
Dergach A. Formation of a Favorable Investment Climate (Britain after Brexit and Others) / A. Dergach, О. Kibik, S. Skrypnyk et al. // AD ALTA: Journal of Interdisciplinary Research. - Vol. 11. - Iss. 2. - Magnanimitas Assn., 2021. - Р. 107-111.
Keywords: foreign investment; investment climate; investment policy; EU investments; іноземні інвестиції; інвестиційний клімат; інвестиційна політика; інвестиції ЄС; Research Subject Categories::SOCIAL SCIENCES::Business and economics::Economics